The Quality of Measurements A Metrological Reference - Fridman, A.E.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
This book provides a detailed discussion and commentary on the fundamentals of metrology. The fundamentals of metrology, the principles underlying the design of the SI International System of units, the theory of measurement error, a new methodology for estimation of measurement accuracy based on uncertainty, and methods for reduction of measured results and estimation of measurement uncertainty are all discussed from a modern point of view. The concept of uncertainty is shown to be consistent with the classical theory of accuracy. The theory of random measurement errors is supplemented by a very general description based on the generalized normal distribution; systematic instrumental error is described in terms of a methodology for normalizing the metrological characteristics of measuring instruments. A new international system for assuring uniformity of measurements based on agreements between national metrological institutes is discussed, in addition to the role and procedure for performance of key comparisons between national standards. The conclusion describes a new methodology for assurance of measurement accuracy (based on the provisions contained in the ISO 5725-series standards) that is now becoming more and more common around the world. All of the theoretical statements and calculation methods are illustrated using examples. This book will be of interest to personnel working in government metrological services (or in the metrological services of legal entities), and to specialists who use measuring instruments or make use of measured data in their daily activities It will be useful to students at technical universities when studying the academic disciplines of Metrology, Standardization, and Certification; Metrology and Measurement Assurance; and Metrology and Measuring Instruments.
Preface -- From the Author -- 1. Basic Concepts of Metrology -- 2. Measurement Errors -- 3. Measurement Uncertainty -- 4. Methods for Estimation of Measurement Results and Their Uncertainties -- 5. International System of Units SI -- 6. Measurement Assurance -- 7. Verification and Calibration Intervals -- 8. Assurance of Measurement Accuracy in Correspondence with the ISO 5725 Standards -- References -- Index.
Keywords: Physics; Probabilities; Physical measurements; Measurement; Quality control; Reliability; Industrial safety; Physics; Measurement Science and Instrumentation; Quality Control, Reliability, Safety and Risk; Probability Theory and Stochastic Processes; Electronic books